2023
DOI: 10.1093/sleep/zsad308
|View full text |Cite
|
Sign up to set email alerts
|

Sleep deprivation alters pubertal timing in humans and rats: the role of the gut microbiome

Shirley Priscilla Gunawan,
Shih-Yi Huang,
Chun-Chi Wang
et al.

Abstract: Study Objectives Evidence implied that sleeping duration is associated with the timing of puberty and that sleep deprivation triggers early pubertal onset in adolescents. Sleep deprivation can affect metabolic changes and gut microbiota composition. This study investigated the effects of sleep deprivation on pubertal onset and gut microbiota composition in animal models and a human cohort. Methods This study comprised 459 boy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…Climate change, marked by increased greenhouse gas concentrations and reduced natural carbon sinks, leads to higher temperatures. Elevated CO 2 emissions affect soil microbial composition and function, potentially influencing the human gut microbiome through alterations in soil biodiversity that impact food crop quality [ 94 ]. In bats, it was recently reported that hibernation energy requirements could change as an adaptation to a warmer climate [ 95 ].…”
Section: Gut Microbiota Changes Due To Changes In the Environmentmentioning
confidence: 99%
“…Climate change, marked by increased greenhouse gas concentrations and reduced natural carbon sinks, leads to higher temperatures. Elevated CO 2 emissions affect soil microbial composition and function, potentially influencing the human gut microbiome through alterations in soil biodiversity that impact food crop quality [ 94 ]. In bats, it was recently reported that hibernation energy requirements could change as an adaptation to a warmer climate [ 95 ].…”
Section: Gut Microbiota Changes Due To Changes In the Environmentmentioning
confidence: 99%